MONITORING AND ANALYSIS OF THE COMPOSITION OF PM2.5 IN LAHORE, PAKISTAN (Pakistan Journal of Science, 2023)
Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and Lahore is grappling with severe air pollution, exacerbated by its rapid urban and industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. industrial expansion. Regulatory oversight on vehicular and emissions remains weak. Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures (Meteorological conditions, especially during winter with its low temperatures ( Meteorological conditions, especially during winter with its low temperatures (around 20 around 20around 20around 20around 20around 20around 20around 20-30°C), 30°C), 30°C), 30°C), 30°C), 30°C), stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the stagnant winds, and lack of rain, trap pollutants, creating a smoggy environment. November sees the peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher peak in PM2.5 concentration at 222 µg/m3. Conversely, summer brings relief due to higher temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 temperatures, rainfall, and winds, reducing PM2.5 levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around levels to as low 31 µg/m3 in August. Around 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent 26% of PM2.5 is made up sulfate and nitrate. The latter's concentration higher due to prevalent sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation sources like vehicles and industrial outputs. This dominance of nitrate indicates that transportation households are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in ouseholds are primary contributors to the city's air pollution, even more so than industries. Drains in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in Lahore, filled with untreated wastewater, are a significant source of the 16% ammonium found in PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres PM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial presPM2.5. Natural dust is evident from the substantial pres ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. ence of Si (12.6%), Ca, and Fe in PM2.5. Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in industries households, contribute Emissions from vehicle exhausts and fossil fuel burning, both in indust